KORUPSI, ANGGARAN, DAN MASYARAKAT: SEBUAH CINTA TERLARANG - Henni Mande (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The writing aims to analyze the extent of the role of society in the occurrence of corruption. The method used is qualitative descriptive. The findings of this research, first of all, is that the community plays a role in corruption because community behavior in the form of